Financial statement analysis - Subramanyam, K. R. (New York, NY : McGraw Hill Education, 2014)
Emphasizes effective business analysis and decision making by various stakeholders of the company. This book begins with an overview, followed by accounting analysis and then financial analysis. It presents a balanced view of analysis, including both equity and credit analysis, and both cash-based and ea
Chapter 1: Overview of Financial Statement Analysis Chapter 2: Financial Reporting and Analysis Chapter 3: Analyzing Financing Activities Chapter 4: Analyzing Investing Activities Chapter 5: Analyzing Investing Activities: Intercorporate Investments Chapter 6: Analyzing Operating Activities Chapter 7: Cash Flow Analysis Chapter 8: Return on Invested Capital and Profitability Analysis Chapter 9: Prospective Analysis Chapter 10: Credit Analysis Chapter 11: Equity Analysis and Valuation Comprehensive Case: Applying Financial Statement Analysis Appendix A Financial Statements Colgate Palmolive Co. Campbell Soup
Keywords: Financial statements